Did the Affordable Care Act Decrease Veteran Enrollment in the Veterans Health Administration?. Issue 8 (August 2020) - Silva, Abigail; Tarlov, Elizabeth; Gonzalez, Beverly; Smith, Bridget M.; French, Dustin D.; Hogan, Timothy P.; Jordan, Neil; Huo, Zhiping; Martinez, Rachael N.; Ippolito, Dolores; Stroupe, Kevin T.
Abstract : Background: Provisions of the Affordable Care Act (ACA) provided nonelderly individuals, including Veterans, with additional health care coverage options. This may impact enrollment for health care through the Veterans Health Administration (VHA). National enrollment data was used to: (1) compare characteristics of enrollees at 3 time points in relation to the implementation of ACA insurance provisions (2012); and (2) examine enrollment trends. Methods: The study population included a 10% sample of Veterans under age 65 who were VHA enrollees between January 2012 and September 2015. Demographic and baseline characteristics were compared between 3 enrollment groups: pre-2012, pre-ACA (2012–2013), and post-ACA (2014–2015). Using an interrupted time series approach, we employed pooled logistic regression to assess trends in new VHA enrollment, overall, and by select enrollee characteristics. Results: A total of 429, 833 enrollees were identified. Compared with pre-ACA enrollees, post-ACA enrollees were more likely to be older, have a service-connected disability, live further away from a VHA medical center, but less likely to use primary care within 6 months. The post-ACA quarterly trend in the odds of being a new enrollee was 3% lower (95% confidence interval: 0.96, 0.98) as compared with the pre-ACA trend. This decline was consistent across sex, geography, (all but 1) priority group, and state Medicaid-expansion subgroups. Conclusions: The ACA appears to have contributed to a decline in new VHA enrollment. In addition, the profile of newer enrollees differs from that of pre-ACA enrollees. The VHA must continue to monitor trends in demand in order to continue delivering high-quality, efficient care. Abstract : Supplemental Digital Content is available in the text.